Impact of Interplanetary Coronal Mass Ejections (ICMEs) and Corotating Interaction Regions (CIRs) on Galactic Cosmic Ray Intensity and Space Weather Parameters (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The Sun, the central powerhouse of our solar system, exerts profound influence over both the global environment and the broader cosmos. Among its many phenomena, the solar wind, a continuous flow of charged particles, plays a critical role in shaping the heliosphere—a vast bubble that extends far beyond the solar system and serves as a protective shield against cosmic rays. This study explores the intricate dynamics between solar wind structures, particularly Interplanetary Coronal Mass Ejections (ICMEs) and Corotating Interaction Regions (CIRs) and their impact on Galactic Cosmic Ray (GCR) intensity. Using data from 2000 to 2023, we analyze the behavior of various plasma and field parameters during the passage of ICMEs and CIRs, with a focus on those associated with shock events. Our findings indicate that shock-associated ICMEs significantly enhance geomagnetic activity, leading to more pronounced declines in GCR intensity compared to non-shock ICMEs. The study also highlights the variations in key space weather parameters across different interplanetary structures, offering valuable insights into the complex interactions between the Sun and the space environment.